Construction of Schisandra Chinensis Cloud Medicine Database Based on Big Data - Lin, Yuqi; Liu, Junxia (2023 International Conference on Industrial IoT, Big Data and Supply Chain (IIoTBDSC), 2023)
Schisandra chinensis cloud medicinal database is established for achieving digitalization of Schisandra chinensis supply and demand status, intelligent docking of Schisandra chinensis supply and demand, and enhance preventive nature of Schisandra chinensis preparation and timely supplementation. Firstly, basic framwork of Schisandra chinensis cloud medicinal database is designed, and function modules of database are established. Schisandra chinensis cloud medicinal database based on big data technology is designed. Standard specification system and safety guarantee system are confirmed, and application layer, data collection and processing layer, and perception layer and network layer are designed. And big data mining algorithm is established based on Gaussian clustering algorithm, and simulation analysis is carried out for data collection of Schisandra chinensis cloud medicinal database, in addition, relationship between Schisandra chinensis and other medicines is obtained. results show that proposed Schisandra chinensis cloud medicinal database can effectively improve Schisandra chinensis big data management quality.